Democracy on Reserved Terms: Gender Quotas, Institutional Power, and Women’s Representation in Tanzania (2020–2025) - Ruhangisa, Valentine Flavian; Mariyah, Chusnul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This paper is a critical academic analysis of the institutional consequences of the gender quota mechanism in Tanzania in terms of empowering women and giving them democratic representation in politics within the time frame of 2020-2025. Though, the provision of the reserved seats has made women numerically a great presence in the parliament, there remain doubts about how these women have substantive powers, political independence, as well as their democratic right to be. The paper utilizes qualitative institutional analysis to investigate the constitution, electoral, parliamentary, party, and legislative data to evaluate the impact of institutional design on political power and responsibility. The results prove the existence of hierarchical representation and the undermining of electoral accountability and agency of women by the indirect selection mechanisms and the resultant paradox of formal inclusion and substantive marginalization. This institutional organization creates a sort of constrained participation in the democratic process, in which the representation of women is still visible symbolically, but structurally constrained. The study concludes that effective political empowerment must manifest itself through institutional changes that incorporate women into the electoral processes that are based on constituencies, democratize the system of nominating party candidates, and create greater access to leadership. These reforms are necessary in order to make numerical inclusion substantive democratic representation and to make the government more gender responsive.